CHAQ2020 - Hope Bay - Photographic data - CHAQ2020 - Hope Bay - Orthophotos - Westin, Jonathan; Almevik, Gunnar (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the photographic material and the panoramas from Hope Bay.

The high resolution orthophotos of the shelter (1 mm per pixel) were created with Agisoft Metashape and structure-from-motion photography taken with a Fujifilm X-T2 camera on January 31, 2020. The photos for the high resolution orthophoto of the site Base Esperanza (10 mm per pixel) were taken with a DJI Phantom 4 drone at 150 meters height on January 31 2020, and then processed in Agisoft Metashape.

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar fotografier och panoraman från Hoppets Vik.

Se den engelska beskrivningen för mer information.

Ortofotona av stenhyddan (1 mm per pixel) skapades med Agisoft Metashape och structure-from-motion fotografering som togs med en Fujifilm X-T2-kamera den 31 januari 2020. Fotografierna för ortofotot av Esperanzabasen (10 mm per pixel) togs med en DJI Phantom 4-drönare på 150 meters höjd den 31 januari 2020 och bearbetades sedan i Agisoft Metashape.
CHAQ2020 - Hoppets vik - Fotografiska data - CHAQ2020 - Hoppets vik - Ortofoton
Keywords: Antarctica; Antarktis; Antarctic region; Adélie penguin (Pygoscelis adeliae); Adéliepingvin (Pygoscelis adeliae); Chinstrap penguin (Pygoscelis antarcticus); Hakremspingvin (Pygoscelis antarcticus); Gentoo penguin (Pygoscelis papua); Åsnepingvin (Pygoscelis papua); Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; History and Archaeology; Historia och arkeologi